Impact of educational level on rheumatoid arthritis: A systematic review (2014)
Methods: A systematic review was performed using PubMed, SciELO and LILACS as data bases in order to identify original articles written in English, Portuguese or Spanish that used accepted classification criteria for rheumatoid arthritis and a comparison was made between educational level and outcomes of rheumatoid arthritis. Final articles were identified by two independent reviewers and three blinded reviewers created a new list and extracted data from selected studies. Each record was classified based on the quality score of the studies.Results: Through the systematic review of the literature, the factors and outcomes related to educational level and rheumatoid arthritis identified were: the risk of developing the disease, radiographic progression, depression and anxiety, work disability, functional disability, quality of life, and mortality.Conclusion: The information available in the literature about the impact of the educational level in several outcomes related to rheumatoid arthritisis variable. Only work disability is an outcome related to a low education level in all the articles reviewed.Objectives: To assess the impact of educational level on rheumatoid arthritis through a systematic review of the literature and assessing the age at onset, the educational level as risk factor, and to identify outcomes related to educational level and rheumatoid arthritis. © 2013 Asociación Colombiana de Reumatología. Published by Elsevier España, S.L.U. Todos los derechos reservados.